2018
DOI: 10.22219/jpbi.v4i1.5354
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of students’ science motivation and nature of science comprehension in middle school

Abstract: The purpose of this study was to explore the pattern of science motivation and nature of science (NoS) and the relationship between science motivation and nature of science in middle school students located in Semarang, Central Java, Indonesia. The design of this study was survey followed by the correlation study to discover the relationship between science motivation level and nature of science comprehension. This research included 113 students as sample. The instrument used for data collection was SMQ and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 17 publications
2
15
0
4
Order By: Relevance
“…The above assumptions are in line with some previous studies which reported that the low communication skill can be caused by the both external and internal factors: 1) the low learning motivation of students (Filak & Sheldon, 2008;Kitsantas & Zimmerman, 1998;Nurwidodo, Hendayana, Hindun, & Sarimanah, 2018;Wicaksono, Minarti, & Roshayanti, 2018), 2) the students' passive habit in learning, 3) the low ability in mastering language components, 4) the low quality of students' mentality, 5) the bad interactions between teacher and students (Hodge & Anderson, 2007), 6) the low interaction quality among students, and 7) the improper learning media utilized by teacher (Firdausi, Prabawa, & Sutarno, 2017;Putra, Abdurrahman, & Suana, 2015;Spiliotopoulos, Antonakaki, Ioannidis, & Fragopoulou, 2016) Students' communication skill can be optimized through various ways. Cholvistaria, (2012); Siska et al (2013);and Tuada et al (2017) stated that to enact this skill, students could be motivated to implement science process in their daily communication particularly during discussion and presentation sessions.…”
Section: Students' Scientific Process Skills In West Ilirsupporting
confidence: 90%
“…The above assumptions are in line with some previous studies which reported that the low communication skill can be caused by the both external and internal factors: 1) the low learning motivation of students (Filak & Sheldon, 2008;Kitsantas & Zimmerman, 1998;Nurwidodo, Hendayana, Hindun, & Sarimanah, 2018;Wicaksono, Minarti, & Roshayanti, 2018), 2) the students' passive habit in learning, 3) the low ability in mastering language components, 4) the low quality of students' mentality, 5) the bad interactions between teacher and students (Hodge & Anderson, 2007), 6) the low interaction quality among students, and 7) the improper learning media utilized by teacher (Firdausi, Prabawa, & Sutarno, 2017;Putra, Abdurrahman, & Suana, 2015;Spiliotopoulos, Antonakaki, Ioannidis, & Fragopoulou, 2016) Students' communication skill can be optimized through various ways. Cholvistaria, (2012); Siska et al (2013);and Tuada et al (2017) stated that to enact this skill, students could be motivated to implement science process in their daily communication particularly during discussion and presentation sessions.…”
Section: Students' Scientific Process Skills In West Ilirsupporting
confidence: 90%
“…Learning motivation is able to direct students in looking at learning objects and activating thinking skills that have an impact on learning outcomes. This is in accordance with Wicaksono, Minarti, and Roshayanti (2018) which says that motivation affects students' behavior in achieving their learning goals. Students who are intrinsically motivated will work hard and learn more because there is an inner urge to achieve their goals.…”
Section: Introductionsupporting
confidence: 90%
“…Apparently, environmental problems become one of the interesting aspects of learning. Based on the results of the study it was found that students also have concern for environmental issues (Wicaksono, Minarti, & Roshayanti, 2018). This is what makes this waste plastic waste processing into one of the things that appeal to students.…”
Section: Resultsmentioning
confidence: 98%